2014
DOI: 10.1371/journal.pone.0111590
|View full text |Cite
|
Sign up to set email alerts
|

Screening the Expression of ABCB6 in Erythrocytes Reveals an Unexpectedly High Frequency of Lan Mutations in Healthy Individuals

Abstract: Lan is a high-incidence blood group antigen expressed in more than 99.9% of the population. Identification of the human ABC transporter ABCB6 as the molecular basis of Lan has opened the way for studies assessing the relation of ABCB6 function and expression to health and disease. To date, 34 ABCB6 sequence variants have been described in association with reduced ABCB6 expression based on the genotyping of stored blood showing weak or no reactivity with anti-Lan antibodies. In the present study we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…According to our previous experience, strongly reduced RBC expression levels of the ABCG2 [7] and the ABCB6 [8] membrane proteins were connected to specific mutations and/or polymorphisms in the coding genes. Therefore, we analyzed the DNA extracts of the blood samples of the volunteers with low RBCPMCA4b expression by Sanger sequencing of the ATP2B4 gene, coding for this protein.…”
Section: 3mentioning
confidence: 95%
See 1 more Smart Citation
“…According to our previous experience, strongly reduced RBC expression levels of the ABCG2 [7] and the ABCB6 [8] membrane proteins were connected to specific mutations and/or polymorphisms in the coding genes. Therefore, we analyzed the DNA extracts of the blood samples of the volunteers with low RBCPMCA4b expression by Sanger sequencing of the ATP2B4 gene, coding for this protein.…”
Section: 3mentioning
confidence: 95%
“…RBC membrane protein determinations were carried out according to our recently developed method [6][7][8][9]. In brief, we fixed and permeabilized the RBC membranes by using 1% formaldehyde solution, resulting in RBC "ghosts", and then equal number of cells were incubated with the PMCA-specific primary antibody (JA3, mouse monoclonal antibody, RRID: AB 628160) followed by a secondary, Alexa Fluor 488 labeled goat anti-mouse (H + L) antibody (Thermo Fisher/Life Technologies), in 96 well plates.…”
Section: Rbc Membrane Protein Studiesmentioning
confidence: 99%
“…Through screening erythroid ABCB6 expression, Koszarska et al found an unexpectedly high frequency of Lan mutations in healthy individuals. 21 Indeed, in public databases (1000 Genomes, NHLBI Exome Sequencing Project, Exome Aggregation Consortium) the allele frequencies of V454A, R723Q and R276W are 0.43%, 0.08% and 1.5%, respectively. Moreover, the high frequency of ABCB6 variations in FP, including two FP patients found in a Cardiff blood donor cohort recently described by Bawazir et al, 22 has clinical implications for blood transfusion screening and practice.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects were adult volunteers at the age of over 18 years living in Poland, who donated saliva samples to the Biobank Lab at the Department of Molecular Biophysics of the University of Lodz. Sample collection and anthropological data acquisition through a questionnaire were performed as previously described (Koszarska et al, 2014; Strapagiel et al, 2016). For this study, 186 subjects were randomly chosen and categorised into three distinct groups according to their declared, self-assessed natural hair colour.…”
Section: Methodsmentioning
confidence: 99%
“…The isolation of the genomic DNA from saliva was performed as previously reported (Koszarska et al, 2014). Genotyping of the variants within the studied genes (Table 2) was performed with the HRM (High Resolution Melt) method accompanied by direct sequencing.…”
Section: Methodsmentioning
confidence: 99%